First Report of the Bicolored Ant Tetraponera rufonigra Jerdon on Aquilaria malaccensis Tree - Khakhlari, Arup; Sen, Supriyo (Indian Forester, 2023)
The formation of the tunnels due to feeding by the insect Zeuzera conferta Walker in Aquilaria malaccensis Lam, a critically endangered tree, facilitates harbouring space for some insects that are yet to be studied in the context of the host environment. This is the first report of the association of the bicolored ant, Tetraponera rufonigra Jerdon with the Aquilaria malaccensis tree, which is commonly known as agarwood. The ant is an issue for agarwood tree producers in Assam, India, especially during the extraction process of the resinous agarwood due to stinging attacks. The ant was identified using mitochondrial cytochrome c oxidase subunit I (COXI) gene sequencing. In the tunnels, the agarwood tree provides nesting space for the ants, and the ants may respond by guarding the tree from herbivores. If this particular relationship of the ant T. rufonigra is confirmed by future research, it could lead to new insights into the formation of agarwood resins as a result of insect activity.